Talent Development in Young Cross-Country Skiers: Longitudinal Analysis of Anthropometric and Physiological Characteristics - Zoppirolli, Chiara; Modena, Roberto; Fornasiero, Alessandro; Bortolan, Lorenzo; Skafidas, Spyros; Savoldelli, Aldo; Schena, Federico; Pellegrini, Barbara (Frontiers in Sports and Active Living, 2020)
Introduction: Very little is known about talent development and selection processes in young cross-country skiers. Aim: (1) to analyze the effect of age on anthropometric and physiological parameters in medium-to-high level cross-country skiers during the late teenage period; (2) to describe parameters' trend in selected talents after the late teenage period; (3) to define which characteristics during the late teenage period could discriminate against further talent selection. Method: We found 14 male (M) and nine (F) athletes in our database, identified as talents by regional teams during the late teenage period, who performed the same diagonal-stride roller-skiing incremental test to exhaustion at 17 and 18 years old. Of these, four M and three F teenagers performed four further evaluations, and were selected by the national team. Age effect during the late teenage period was verified on anthropometric and physiological parameters measured at maximal intensity (MAX), first (VT1), and second (VT2) ventilatory thresholds, and 3° and 6° of treadmill incline. An observational analysis allowed to evaluate parameters' trend after the late teenage period in selected athletes, and to determine possible characteristics early discriminating further selection. Results: During the late teenage period, height, weight, and BMI was still raising in M as well as V'O2 at VT2 and 6° of treadmill incline (all P > 0.05). In F, mass-scaled V'O2 MAX increased while heart rate (HR) at MAX and VT2 decreased (all P > 0.05). Since the late teenage period, all selected males showed maximal ventilation volumes, absolute V'O2 at MAX, VT1, and VT2 that were within or above the 75th percentile of their group; the same was found in selected females for mass-scaled V'O2 MAX, VT1, and VT2 time. After the late teenage period, all selected athletes showed an increasing trend for VT2 time, while a decreasing trend for sub-maximal energetic cost, %V'O2 and HR. Discussion: During the late teenage period, males are still completing their maturation process. Since the late teenage period, some physiological parameters seem good indicators to early discriminate for further talents. A progressive increase in skiing efficiency was demonstrated in developing talents of both sexes after the late teenage period.